Management and organization paradoxes - Clegg, Stewart (Advances in organization studies, 2002)
Paradox -- the simultaneous existence of two inconsistent states -- has become orthodox. The orthodox is now the paradox. The orthodox world of ordering, controlling and organizing is increasingly opposed to a normalizing world of disordering, disrupting and disorganizing. And organization studies cannot avoid changing its conceptions of reality as that reality changes. In the future, organization studies will be the study of paradox, how to understand it, how to use it. In this book of original contributions addressed to management and organization paradoxes the authors address the new state of.